Genetic Analysis of Restriction Fragment Length Polymorphism of TLL1 Gene (rs17047200) in Patients of Hepatocellular Carcinoma: RFLP of TLL1 gene - Saima Sharif; Sadia Ashraf; Shagufta Naz; Sher Zaman Saf; Muhammad Saqib (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2022)
To find out the association of polymorphism of the TLL1 gene in hepatocellular carcinoma. A cross-sectional study was conducted from January 2020 to September 2020. Subjects were enrolled from Mayo Hospital, Lahore, Jinnah Hospital Lahore and the Liver Transplant Unit of Sheikh Zayed Hospital, Lahore. A total of 200 individuals were registered and segregated into the Control group (n=100) and hepatocellular carcinoma (HCC) group (n=100). DNA was extracted from obtained blood samples and Restriction Fragments Length Polymorphism (RFLP) was carried out at the laboratories of LCWU by using specific primers and restriction endonuclease enzymes. The data were analyzed statistically. The high proportion of smoking, hepatitis B, hepatitis C, cirrhosis and Body Mass Index (BMI) were established risk factors in the HCC group. Subjects with hepatocellular carcinoma had low socioeconomic status. Heterozygous bands in the HCC group were observed after RFLP. TLL1 genotype was AA (72 %) and AT/TT (28 %). The patient’s clinical aspects were similar across TLL1 genotypes. It was concluded that RFLP on the exon region by using their specific enzymes HpyCH4III showed heterozygous bands in the HCC group that indicated a mutation in the TLL1 gene though this mutation does have a significant association with HCC.